Clinical efficacy of high-dose dexamethasone with sequential prednisone maintenance therapy for newly diagnosed adult immune thrombocytopenia in a real-world setting. Issue 4 (April 2021) - Xu, Jin; Zhang, Xinhui; Feng, Shanglong; Zhao, Na; Hu, Xin; Cheng, Yaxin; Wu, Yue; Zhou, Li; Tong, Juan; Zheng, Changcheng
Objective: As first-line treatments for newly diagnosed adult immune thrombocytopenia (ITP), high-dose dexamethasone (HD-DXM) and conventional-dose prednisone achieve good initial responses, but their long-term efficacy is poor. To improve the long-term outcome of newly diagnosed ITP, we explored the efficacy and safety of HD-DXM with sequential prednisone maintenance therapy. Methods: This retrospective study in a real-world setting assessed 72 consecutive newly diagnosed ITP patients administered first-line HD-DXM with sequential prednisone maintenance therapy from 1 June 2016 to 31 December 2019. Results: Seventy patients obtained response (97.2%), and 55 achieved sustained response (SR) (76.4%). Fifty-three obtained complete remission (CR) (73.6%), and 39 achieved continuous CR at 6 months (54.2%). Among 36 anti-nuclear antibody-positive patients, 100% achieved response, and 28 achieved CR (77.8%). Among 24 antithyroid antibody-positive patients, 23 (95.8%) achieved response, and 20 achieved CR (83.3%). For patients with initial response, the 12-month probability of SR was 78.6%. For patients with initial CR, the 12-month probability of continuous CR was 64.2%. At 12 months, 21.4% of patients with initial response and 11.3% of patients with initial CR showed loss of treatment response. Conclusions: HD-DXM with sequential prednisone as the first-line treatment for newly diagnosed ITP patients may achieve good clinical efficacy.